2008
DOI: 10.1186/1741-7007-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate gene expression in allopolyploid Gossypiumreveals two temporally distinct phases of expression evolution

Abstract: Background: Polyploidy has played a prominent role in shaping the genomic architecture of the angiosperms. Through allopolyploidization, several modern Gossypium (cotton) species contain two divergent, although largely redundant genomes. Owing to this redundancy, these genomes can play host to an array of evolutionary processes that act on duplicate genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
235
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(267 citation statements)
references
References 44 publications
(56 reference statements)
24
235
2
2
Order By: Relevance
“…The short read lengths of next-generation sequencing hinder assembly through complex regions, and fragmented draft and reference genomes usually lack skewed (G+C)-content sequences and repetitive intergenic sequences. Furthermore, in allopolyploid species, homoeolog expression dominance or bias, and specifically differential homoelog gene expression, has often been detected, for instance in Gossypium [15][16][17] Triticum 18,19 and Arabidopsis 20,21 , but the role of this phenomenon in selection for phenotypic traits remains mechanistically mysterious 22 .…”
Section: 5mentioning
confidence: 99%
“…The short read lengths of next-generation sequencing hinder assembly through complex regions, and fragmented draft and reference genomes usually lack skewed (G+C)-content sequences and repetitive intergenic sequences. Furthermore, in allopolyploid species, homoeolog expression dominance or bias, and specifically differential homoelog gene expression, has often been detected, for instance in Gossypium [15][16][17] Triticum 18,19 and Arabidopsis 20,21 , but the role of this phenomenon in selection for phenotypic traits remains mechanistically mysterious 22 .…”
Section: 5mentioning
confidence: 99%
“…Moreover, interactions between Aa trans factors and cis elements of At alleles or vice versa result in up-or down-regulation of At and Aa alleles. This may explain at least in part why different dominant expression patterns were identified in the same 8,40 or different allopolyploids 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Barbara McClintock 6 coined the term 'genome shock' to describe unprepared changes to cope with an existing programmed response in interspecific hybrids, leading to transposon activation and genomic instability. Recent studies have shown that genome hybridization between species also induces novel changes in geneexpression 'shock' , as observed in many allopolyploids including Arabidopsis 7 , cotton 8 , and Senecio 9 . The induced variation in the interspecific hybrids can be transmitted to the progeny if chromosomes are doubled to form stable allopolyploids 5,10 .…”
mentioning
confidence: 99%
“…Upland cotton was formed by ancient interspecific hybridization between AA and DD genome species. In a large microarray study of ovular tissue, Yang et al (2006) demonstrated that AA subgenome genes of all functional classifications were selectively enriched in G. hirsutum L., whereas in a recent study of petal tissues, Flagel et al (2008) encountered the opposite generalized bias and concluded that neither Gossypium genome is globally dominant with respect to expression, but rather, each genome may have local dominance in certain tissue types or developmental stages. Therefore, transcriptome dominance is probably a general consequence of hybridization effects on gene expression in interspecific hybrids and allopolyploids, and seems to be potentially oriented differently in different organs as a probable result of subfunctionalization of duplicated genes (Lynch and Force, 2000).…”
Section: Discussionmentioning
confidence: 99%